Cyclic AMP-Dependent Regulation of Kv7 Voltage-Gated Potassium Channels - van der Horst, Jennifer; Greenwood, Iain A.; Jepps, Thomas A. (Frontiers in Physiology, 2020)
Voltage-gated Kv7 potassium channels, encoded by KCNQ genes, have major physiological impacts cardiac myocytes, neurons, epithelial cells, and smooth muscle cells. Cyclic adenosine monophosphate (cAMP), a well-known intracellular secondary messenger, can activate numerous downstream effector proteins, generating downstream signaling pathways that regulate many functions in cells. A role for cAMP in ion channel regulation has been established, and recent findings show that cAMP signaling plays a role in Kv7 channel regulation. Although cAMP signaling is recognized to regulate Kv7 channels, the precise molecular mechanism behind the cAMP-dependent regulation of Kv7 channels is complex. This review will summarize recent research findings that support the mechanisms of cAMP-dependent regulation of Kv7 channels.